The Aesthetic Power of Dhwani: Bridging Sound and Sense in Poetic Expression - Bari, Kartick Chandra (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This paper examines the aesthetic potency of dhwani (suggestion) in classical Sanskrit poetics, emphasizing its function in connecting sound and meaning in poetic expression. Introduced by philosopher and critic Anandavardhana in his Dhwanaloka, dhwani highlights the indirect, evocative meanings generated by the phonetic attributes of words, surpassing their literal interpretations. This study underscores the importance of dhwani in conveying profound feelings and intricate concepts, hence enriching the emotional depth and interpretative potential of poetry. The paper examines the relationship between dhwani and the notion of rasa (aesthetic taste), illustrating how sound, meaning, and emotion coalesce to produce a complex, layered experience for the reader. This paper conducts a critical analysis of traditional writings, particularly those by Kālidāsa, highlighting the lasting significance of dhwani in comprehending the intricate relationship between language and creative expression. This research enhances broader dialogues in literary theory, linguistics, and translation studies, providing insights into the influence of indirect suggestion on the craft of poetry.